Going Beyond Traditional Applications? The Potential of Hydrogels. Issue 1 (24th September 2018) - Zhang, Zhong‐Xing; Young, David James; Li, Zibiao; Loh, Xian Jun
Abstract: Herein are summarized recent trends in the use of hydrogels in robotics, electronics, actuators, and sensors. Two major gaps that limit the application of hydrogels in these fields are discussed, including hydrogels' inherent mechanical weaknesses and poor durability. Possible solutions to these problems include the introduction of self‐healing and the integration of biology inspired reinforcement mechanisms into synthetic systems. Enhancing hydrogels' water retention and interface bonding with other types of solid materials (such as glass, ceramics, metals, and elastomers) are also discussed. Addressing these latter issues is critical to the integration of hydrogels with other components in soft devices. It is argued that rapid, self‐healing, and mechanically strong biomimetic hydrogels will be an important material for the future. Realizing this goal will lead to new kinds of soft materials, new families of hydrogel‐based devices, and exciting new applications.